Author Disambiguation in the Domain of Scholarly Literature - Krygielová, Magdaléna (Vysoké učení technické v Brně. Fakulta informačních technologií, 2013)
Tato práce se zabývá desambiguací autorů v databázích odborné literatury. Z důvodu nejednoznačnosti jmen autorů se v těchto databázích vyskytují problémy s přisuzováním autorství publikací a tím spojenou analýzou citací, vlivu autorů apod.  Tato práce se zabývá otázkou odhadu správného počtu autorů a zkoumá možnosti použití již existujících služeb. Součástí této práce je návrh metody pro desambiguaci autorů. Tato metoda byla implementována a evaluována v rámci systému CORE.

In this project I address the issue of author disambiguation in scholarly literature. This research area finds its use mainly in search engines for scholarly literature, aggregators, etc. The name ambiguity causes problems mainly in citation analysis or analysing of author impact. This project discusses an issue of finding the correct number of distinct authors.  It also discusses a potential use of APIs of existing systems. As a part of this project, a method for author disambiguation in a digital library has been designed. The designed method has been implemented and evaluated in the context of the CORE system.
Author Disambiguation in the Domain of Scholarly Literature
Keywords: desambiguace autorů; CORE; digitální knihovna; shlukování; author disambiguation; CORE; digital library; clustering